Exploration of Accountability Practices: A Study of the Secretariat of the House of Representatives - Budi Santoso, Priyo (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
The review explores the significance of the SAKIP System, focusing on the Secretariat General of the Indonesian House of Representatives, examining both practical and theoretical aspects. An accountability index of 67.46 emerged, resulting in a